MODULATORY EFFECT OF PERIOSTRACUM CICADAE AND BETULAE CORTEX EXTRACTS ON THE ACTIVATION OF ATOPIC DERMATITIS-RELATED ION CHANNELS ORAI1 AND TRPV3 - Nam, Joo Hyun; Jung, Hyo Won; Kim, Woo Kyung; Bae, Hyo Sang (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The cast-off shells of Cryptotympana pustulata (Periostracum Cicadae, PC) and the bark of Betula platyphylla (Betulae Cortex, BC) are used as traditional medicines for the treatment of skin diseases. This study was conducted to investigate the regulatory effects of PC and BC extracts on the activation of the ion channels, calcium release-activated calcium channel protein 1 (ORAI1) and transient receptor potential cation channel subfamily V member 3 (TRPV3). Materials and Methods: Human HEK293T cells, co-overexpressing ORAI1/stromal interaction molecule 1 (STIM1) or overexpressing TRPV3, were treated with PC or BC extracts at 0.1 mg/mL. The changes in ORAI1 and TRPV3 activities were measured using a conventional whole-cell patch-clamp technique. Results: PC and BC extracts significantly decreased ORAI1 activation in ORAI1-STIM1 co-overexpressing HEK293T cells and significantly increased TRPV3 activation in TRPV3 overexpressing cells, compared to that of 2- aminoethoxydiphenyl borate (2-APB, 100 μM), a known agonist of TRPV3. Conclusion: Our results suggest that PC and BC extracts have therapeutic potential to improve skin barrier abnormalities in atopic dermatitis via modulation of ORAI1 and TRPV3 activation.